Transducin Partners Outside the Phototransduction Pathway - Srivastava, Dhiraj; Yadav, Ravi P.; Inamdar, Shivangi M.; Huang, Zhen; Sokolov, Maxim; Boyd, Kimberly; Artemyev, Nikolai O. (Frontiers in Cellular Neuroscience, 2020)
Transducin mediates signal transduction in a classical G protein-coupled receptor (GPCR) phototransduction cascade. Interactions of transducin with the receptor and the effector molecules had been extensively investigated and are currently defined at the atomic level. However, partners and functions of rod transducin α (Gαt1) and βγ (Gβ1γ1) outside the visual pathway are not well-understood. In particular, light-induced redistribution of rod transducin from the outer segment to the inner segment and synaptic terminal (IS/ST) allows Gαt1 and/or Gβ1γ1 to modulate synaptic transmission from rods to rod bipolar cells (RBCs). Protein-protein interactions underlying this modulation are largely unknown. We discuss known interactors of transducin in the rod IS/ST compartment and potential pathways leading to the synaptic effects of light-dispersed Gαt1 and Gβ1γ1. Furthermore, we show that a prominent non-GPCR guanine nucleotide exchange factor (GEF) and a chaperone of Gα subunits, resistance to inhibitors of cholinesterase 8A (Ric-8A) protein, is expressed throughout the retina including photoreceptor cells. Recent structures of Ric-8A alone and in complexes with Gα subunits have illuminated the structural underpinnings of the Ric-8A activities. We generated a mouse model with conditional knockout of Ric-8A in rods in order to begin defining the functional roles of the protein in rod photoreceptors and the retina. Our analysis suggests that Ric-8A is not an obligate chaperone of Gαt1. Further research is needed to investigate probable roles of Ric-8A as a GEF, trafficking chaperone, or a mediator of the synaptic effects of Gαt1.